The status and conservation of the Cape Gannet Morus capensis. (13th December 2019) - Sherley, Richard B; Crawford, Robert JM; Dyer, Bruce M; Kemper, Jessica; Makhado, Azwianewi B; Masotla, Makhudu; Pichegru, Lorien; Pistorius, Pierre A; Roux, Jean-Paul; Ryan, Peter G; Tom, Desmond; Upfold, Leshia; et al.
Abstract : The Cape Gannet Morus capensis is one of several seabird species endemic to the Benguela upwelling ecosystem (BUS) but whose population has recently decreased, leading to an unfavourable IUCN Red List assessment. Application of 'JARA' ('Just Another Red-List Assessment, ' a Bayesian state-space tool used for IUCN Red List assessments) to updated information on the areas occupied by Cape Gannets and the nest densities of breeding birds at their six colonies, suggested that the species should be classified as Vulnerable. However, the rate of decrease of Cape Gannets in their most-recent generation exceeded that of the previous generation, primarily as a result of large decreases at Bird Island, Lambert's Bay, and Malgas Island, off South Africa's west coast (the western part of their range). Since the 1960s, there has been an ongoing redistribution of the species from northwest to southeast around southern Africa, and ∼70% of the population now occurs on the south coast of South Africa, at Bird Island in Algoa Bay, on the eastern border of the BUS. Recruitment rather than adult survival may be limiting the present population; however, information on the seabird's demographic parameters and mortality in fisheries is lacking for colonies in the northern part of the BUS. Presently, major threats to Cape Gannet include: substantially decreased availability of their preferred prey in the west; heavy mortalities of eggs, chicks and fledglings at and around colonies, inflicted by Cape Fur Seals Arctocephalus pusillus and other seabirds; substantial disturbance at colonies caused by Cape Fur Seals attacking adult gannets ashore; oiling; and disease.